Interprofessional Collaboration in Antenatal Care Services among Adolescents with Unintended Pregnancies: A Scoping Review - Viana Bari Umaroh; Sulistyaningsih Sulistyaningsih; Andari Wuri Astuti (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Unplanned pregnancies (UP) among adolescents remain a global public health issue associated with physical, psychological, and social risks. Adolescents often delay seeking antenatal care (ANC), which leads to an increased risk of complications. Interprofessional collaboration (IPC) is recognized as a strategic approach to improving the quality of ANC services. This study aims to explore interprofessional collaborative practices in antenatal care services for adolescents with unintended pregnancies, including institutional support, healthcare workforce competencies, interprofessional communication, collaborative work culture, service support systems, service implementation, and their contribution to the quality of antenatal care services. Method: A scoping review was conducted using the Arksey & O’Malley approach to search the PubMed, ScienceDirect, EBSCO, and Springer databases for relevant articles. The articles were filtered using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flowchart, critically appraised using the Joanna Briggs Institute (JBI) and the Mixed Methods Appraisal Tool (MMAT). Result: Of the 2,060 articles selected for the review, 9 articles met the inclusion criteria. IPC in ANC is implemented through teamwork, integrated services, and cross-sectoral coordination. Key components include clarity of roles, effective communication, and shared decision-making. Supporting factors include institutional policies, resource availability, and workforce competencies. Barriers include fragmented systems, limited resources, and hierarchical communication challenges. Conclusion: IPC improves the quality and comprehensiveness of antenatal care services for adolescents with unplanned pregnancies. Strengthening the policy framework, workforce competencies, and integrated service systems is essential for optimizing collaborative practices